THE PUBLISHING OF BILINGUAL DICTIONARIES IN LITHUANIA (1990–2010) - GAIŽAUSKAITĖ, LINA (Knygotyra, 2012)
The object of this article is the publishing of bilingual dictionaries in Lithuania in 1990−2010. The analysis of nowadays’ users of dictionaries and of scientific and statistical literature helps to predict the future of bilingual dictionaries in conditions of digital lexicography: the usage of traditional dictionaries tends to decrease, while the demand of digital bilingual dictionaries is growing. For this reason, in the presence of a huge number of digital dictionaries, paper dictionaries will be published only in small editions in the near future.